XianLingGuBao protects against osteoporosis through activating STAT3 in vitro and vivo - Zhihua Li; Yongsheng Liu; Li Ren; Yang Sun; Xin Guo; Leiqi Ren; Shancheng Guo; Yuhua Li; Yinbo Niu (Elsevier, 2024)
Background: XianLingGuBao (XLGB) is a potent traditional Chinese patent medicine used to treat osteoporosis (OP), osteoarthritis, aseptic bone necrosis, and other musculoskeletal disorders. The current study aims to identify the active ingredients of XLGB and further elucidate its mechanism on OP treatment. Methods: Experimental pharmacology coupled with network pharmacology methods were used, and the effects of XLGB on mouse osteoblast MC3T3-E1 and ovariectomized (OVX) postmenopausal OP mouse model were detected. Furthermore, ultra performance liquid chromatography tandem quadrupole time of flight mass spectrometry (UPLC Q/TOF MS) was used to identify the active ingredients in XLGB for protecting osteoporosis. Results: XLGB was shown to significantly promote the growth of MC3T3-E1 cells. It could promote the cell proliferation and enhance the formation of mineralized nodule of MC3T3-E1 cells. The efficacy of XLGB in preventing osteoporosis in OVX mice was also demonstrated. The network pharmacological analysis indicated that the top 5 active components of XLGB anti-OP were HX-14, 3-hydroxypsoralen, kaempferol, palmitic acid, and terpene ether. Both KEGG and GO analysis indicated that XLGB may inhibit bone loss through activating the STAT3. Results from the Western blot analysis confirmed that the expression and activity of STAT3 were affected by XLGB. Conclusion: This study clearly demonstrates that the activation of STAT3 plays an crucial role in the protective effect of XLGB against OP. These findings provide a solid experimental foundation on the extensive use of XLGB in the clinical treatment of OP.